Long-Term Survival After Surgery and Radiotherapy for Recurrent or Persistent Ovarian and Tubal Cancer. Issue 6 (1st June 2018) - Rome, Robert; Dipnall, Joanna; Leung, Sam
Abstract : Objective: This study examines the factors associated with long-term disease-specific survival (DSS) and complications after radiotherapy (RT) for recurrent or persistent ovarian and tubal cancer. Methods/Materials: Between 1980 and 2015, 65 women with ovarian (57), tubal (3), or co-existent ovarian/endometrial carcinoma (5) received RT (>45 Gy) with curative intent for recurrent (45) or persistent cancer (20) found at second-look surgery. Surgery to debulk (± restage) was integrated into the management of all but 7 cases. Results: Twenty-two women had no evidence of disease at last contact after a median of 15.6 years (range = 1.0–35.8 years). Of the 53 patients treated more than 10 years ago, 18 (34%) are in this long-term no evidence of disease group. Univariate analysis showed that the following factors were significantly associated with longer DSS ( P < 0.05): initial stage I, II (vs III, IV); endometrioid histology (vs serous and other); no or 1 previous chemotherapy (vs ≥2); no macroscopic tumor before RT (vs macroscopic); localized tumor encompassed by a limited-volume RT field (vs more widespread tumor), and chemotherapy and RT (vs RT only). Multivariate analysis showed that endometrioid (vs other histology HR = 4.37, P = 0.017) and localized tumor (vs more widespread tumor, HR = 2.43, P = 0.017) were significantly associated with longer DSS. After RT to the pelvis and/or abdomen, 13 (21.7%) of 60 patients developed G3 or 4 bowel complications requiring surgery. In 10, these occurred in the presence of tumor, RT changes, and adhesions, and in 3, there was no sign of cancer. Six patients (9.2%) developed a subsequent malignancy. Conclusions: We conclude that there is a role for the use of RT in selected cases of localized recurrent or persistent ovarian cancer and may confer long-term survival. Surgery is useful to debulk and define the extent of tumor to be irradiated but may confer an increased risk of severe bowel complications.